The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s10072-017-3227-8
|View full text |Cite
|
Sign up to set email alerts
|

Chemokines CXCL10, CXCL11, and CXCL13 in acute disseminated encephalomyelitis, non-polio enterovirus aseptic meningitis, and neuroborreliosis: CXCL10 as initial discriminator in diagnostic algorithm?

Abstract: We investigated potential diagnostic usefulness of serum and cerebrospinal fluid (CSF) concentrations of chemokines CXCL10, CXCL11, and CXCL13 in pediatric patients with acute disseminated encephalomyelitis (ADEM) (n = 23), non-polio enterovirus aseptic meningitis (NPEV AM) (n = 20), and neuroborreliosis (NB) (n = 21) and children with acute infectious diseases with neurological symptoms but with excluded neuroinfection/neuroinflammation (controls, n = 20). CSF levels of CXCL10 and CXCL11 were higher in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 32 publications
5
18
0
Order By: Relevance
“…However, most studies measuring CXCL13 using ELISA and lateral flow (LFA) methods have shown elevated CXCL13 circulation levels in the CSF of patients with acute neuroborreliosis compared to other tested groups. Results of the available studies suggest its very high diagnostic value and report its high sensitivity and specificity [5][6][7][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]. These studies are in agreement with a meta-analysis performed by Yang J. et al, who confirmed that CXCL13 has a high sensitivity and specificity for diagnosing neuroborreliosis [68].…”
Section: Cxcl13 Concentrationsupporting
confidence: 85%
See 2 more Smart Citations
“…However, most studies measuring CXCL13 using ELISA and lateral flow (LFA) methods have shown elevated CXCL13 circulation levels in the CSF of patients with acute neuroborreliosis compared to other tested groups. Results of the available studies suggest its very high diagnostic value and report its high sensitivity and specificity [5][6][7][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]. These studies are in agreement with a meta-analysis performed by Yang J. et al, who confirmed that CXCL13 has a high sensitivity and specificity for diagnosing neuroborreliosis [68].…”
Section: Cxcl13 Concentrationsupporting
confidence: 85%
“…These studies have proven that CXCL13 concentration in the CSF of pediatric patients is significantly increased in neuroborreliosis compared to non-neuroborreliosis individuals [8,9,44,47]. One study revealed that differences in CXCL13 levels between children with neuroborreliosis and those with other conditions were statistically significant, although relatively small [45]. CXCL13 also confirmed the diagnosis of possible neuroborreliosis in 100% of patients, indicating a higher diagnostic sensitivity than intrathecal-specific antibodies synthesis [27,48].…”
Section: Cxcl13 In Pediatric Patientsmentioning
confidence: 97%
See 1 more Smart Citation
“…The finding of neutrophil activation in both LNB and EVM is intriguing, since these infections have similarities with respect to both clinical presentation and CSF cellular profile, which may include neutrophil predominance in the early phase [35]. Several studies have de facto shown the presence of neutrophil-activating cytokines and chemokines in the CSF samples of patients with LNB [36][37][38][39] and EVM [40,41], and the production of neutrophil chemo-attractants, such as CXCL1, CXCL8 and CXCL10 after in vitro stimulation of neuronal cells in response to B. burgdorferi spirochaetes [42]. Thus, there appears to be a prerequisite for neutrophil recruitment into the CNS in infections caused by B. burgdorferi and enterovirus.…”
Section: Discussionmentioning
confidence: 99%
“…The chemokine CXCL10, also called interferon (IFN) γ-inducible protein 10 (IP-10), is produced by innate immune cells, such as neutrophils, and it stimulates chemotaxis of mononuclear cells into the CNS in response to meningitis/encephalitis caused by, for instance, enterovirus [43], B. burgdorferi [44], and TBE virus [45]. Furthermore, IP-10 has been proposed as a potential discriminator between bacterial and viral CNS infections [41]. Interestingly, CXCL10 was particularly increased in the EVM group, in which the proportion of polynuclear cells was highest.…”
Section: Discussionmentioning
confidence: 99%